COMPARATIVE EVALUATION OF THE EFFICIENCY AND SAFETY OF TREATING CHILDREN WITH POLYARTICULARY JUVENILE IDIOPATHIC ARTHRITIS WITH METHOTREXATE AND WITH METHOTREXATE COMBINED WITH TOCILIZUMAB - V. A. Kel'tsev; L. I. Grebenkina; E. D. Moiseeva (Union of pediatricians of Russia, 2015)
Substantiation. The Juvenile Idiopathic Arthritis (JIA) is the most frequent rheumatic disease at children and is characterized by primary damage of joints, and also pathology of other bodies and fabrics with formation of polyorgan insufficiency of various degree of expressiveness. Research objective. A comparative assessment of efficiency and safety of a tocilizumab in a combination with a methotrexate in comparison with therapeutic efficiency only a methotrexate at patients with polyarticulary option of JIA. Methods. Kliniko-laboratory, biochemical, immunological methods of a blood test in dynamics of a disease against the carried-out therapy were used. Results. Tocilizumab in combination with a methotrexate has the expressed anti-inflammatory effect at the children sick with polyarticulary option of JIA. At treatment only a methotrexate efficiency of the carried-out therapy was much lower and not always than the effective. Conclusion. Tocilizumab is a perspective preparation for treatment of juvenile arthritis, refractory to standard immunosupressivе therapy.